Thermal Characterization and Stability Analysis of Aqueous Zno-Based Nanofluids Numerically Implemented in Microchannel Heat Sinks - Martinez-Gutierrez, V; Zapata-Ramirez, P; Vasco-Calle, D; Singh, D; Lozano-Steinmetz, F; Chi-Duran, I (Elsevier Ltd, 2021)
Water-based nanofluids prepared with ZnO nanoparticles (⩽17 nm) were characterized. The thermal conductivity and viscosity were measured as a function of temperature (278–303 K), for two ZnO concentration (1wt% and 3wt%) establishing that, whereas the nanofluid prepared with a concentration of 1wt% registered an average improvement of the thermal conductivity of 10.31% at a concentration of 3wt%, the viscosity decreased an average of 5.03% respect to the base fluid. An analysis of the stability of these nanofluids was carried out via UV–vis, finding that for a concentration of 3wt% the stability is better, since it requires 168 h to decrease its absorbance in the same amount as the sample of 1wt%. Additionally, the laminar three-dimensional flow of these nanofluids has been numerically studied considering symmetric microchannels (200 ⩽Re⩽ 1200) of fixed-width rectangular cross-section (283 μm) and three different heights (200 μm, 600 μm, and 400 μm), subjected to a constant heat flux in the lower wall (50 W/cm2). The microchannels have been simulated considering the properties of the nanofluid variable with respect to temperature through experimentally determined models (for 1wt% and 3wt%), finding that thermal conductivity improves mostly for a concentration of 1wt%, registering an increase in average 10.31% in the studied temperature range.The numerical results showed that the use of nanofluids favors heat transfer at low Reynolds numbers with the maximum improvement in the coefficient of heat transfer by convection (42.33%). A decrease in temperature of the base of the microchannel is also observed, which is more significant at low Reynolds numbers for a concentration of 1wt%. In the case of MCH-1 with Re=200, the decrease in the mean temperature of the lower wall is 5.65% (20.45 K), a value that decreases to 0.90% (2.94 K) for Re=1200. This configuration also offers the highest net heat gain, considering the increase in the coefficient of friction produced by the incorporation of ZnO nanoparticles. Finally considering the experimental studies of the thermal properties and stability of nanofluids, and the numerical results associated with the thermal and fluid-dynamic performance of the microchannels, a methodology is proposed to carry out a comprehensive approach to the application of nanofluids in microchannels. © 2020 Elsevier Ltd